" teaching strategies that enable children with autism spectrum disorder " Study using the Meta- analysis method - Dewaishi, Sheymaa (Journal of Educational and Psychological Sciences, 2018)
Augmentative and alternative communication (AAC) contains all methods of communication (other than oral speech) that are used to express thoughts, needs, wants, and ideas. Autism spectrum disorder (ASD) is characterized by difficulties in communication, language, and social communication (Ganz, Earles-Vollrath, Heath, Parker, Rispoli, & Duran, 2012). AAC offers the potential to provide children who have complex communication needs including children with ASD access to the magic and power of communication. This paper is intended to review the research on methods used to identify appropriate teaching strategies that enable children with autism spectrum disorder (ASD) to achieve their communication skills through augmentative and alternative communication (AAC).